Can Grassroots Mobilization of the Poorest Reduce Corruption? A Tale of Governance Reforms and Struggle against Petty Corruption in Bihar, India. Issue 2 (March 2017) - Verma, Rajiv; Gupta, Saurabh; Birner, Regina
ABSTRACT: The rural poor in India have long experienced corruption, exclusion from welfare schemes and the denial of rights. Critical accounts of development policy and practice advocate the need for pro‐poor governance reforms as well as effective mobilization of the poor for exercising their rights and entitlements. However, there is a dearth of empirical work which examines the following questions. What are the dynamics of such mobilization strategies in the environment of pro‐poor governance reforms? How do they affect local power relations from the perspective of the poorest social groups? And what are the challenges involved in sustaining struggles led by civil society organizations on behalf of the poorest and against petty corruption? This article addresses these questions in the context of a grassroots mobilization of Musahars (a Dalit caste group) in Bihar, one of the poorest provinces in India, which has recently initiated pro‐poor governance reforms. It explains what has or hasn't worked (and why) for the Musahars, in terms of their dealings with public officials. The authors argue that pro‐poor governance reforms and welfare schemes on their own are not sufficient; both grassroots mobilization and political will of the ruling dispensation are also necessary.